Simulating ozone degradation of deoxynivalenol and its bio-safety assessment by mouse model - Sun, Chao; Yang, Fang; Xiao, Jianhui; Zhou, Wenwen; Li, Jun; Gu, Xiaolong (Frontiers in Microbiology, 2023)
Deoxynivalenol (DON), a trichothecene mycotoxin, is one of the most prevalent mycotoxins globally, primarily produced by Fusarium species. DON exposure can cause a range of symptoms, including nausea, vomiting, gastroenteritis, growth retardation, immunosuppression, and intestinal flora disorders in both humans and animals. Recently, ozone degradation technology has been applied for DON control.However, the safety of the contaminated grain after degradation was often ignored.Therefore, the implementation technology for assessing the safety of DONcontaminated grain degradation is of great significance for food safety. In this study, based on previous degradation result of DON, we further studied and assessed the toxicity of corn contaminated with ozone-degrading DON by animal experiments in mice. We simulated feed made from corn contaminated with DON produced by inoculated Fusarium graminearum, which was treated with an ozone aqueous solution.DON treated by ozone could effectively increase the expression of total protein in mice and improve the immune system efficacy. Meanwhile, compared with DON directlyexposed mice, the corn with degrading DON could effectively maintain the level of liver and kidney immune function, and improved growth performance, enterohepatic circulation, and energy metabolism. Our study indicated that the toxicity of fed corn contaminated with degrading-DON decreased significantly after ozone degradation, resulting in a much lower toxicity compared to the DON group, or nontoxicity to some extent. Therefore, we hope that this mouse model could be used as a promising approach for assessing the risk of fungal toxins on metabolism, immunity, and intestinal health.